Requirement for interleukin‐1 to drive brain inflammation reveals tissue‐specific mechanisms of innate immunity. Issue 2 (24th November 2014) - Giles, James A.; Greenhalgh, Andrew D.; Davies, Claire L.; Denes, Adam; Shaw, Tovah; Coutts, Graham; Rothwell, Nancy J.; McColl, Barry W.; Allan, Stuart M.
<x xml:space="preserve">Abstract</x> The immune system is implicated in a wide range of disorders affecting the brain and is, therefore, an attractive target for therapy. Interleukin‐1 (IL‐1) is a potent regulator of the innate immune system important for host defense but is also associated with injury and disease in the brain. Here, we show that IL‐1 is a key mediator driving an innate immune response to inflammatory challenge in the mouse brain but is dispensable in extracerebral tissues including the lung and peritoneum. We also demonstrate that IL‐1α is an important ligand contributing to the CNS dependence on IL‐1 and that IL‐1 derived from the CNS compartment (most likely microglia) is the major source driving this effect. These data reveal previously unknown tissue‐specific requirements for IL‐1 in driving innate immunity and suggest that IL‐1‐mediated inflammation in the brain could be selectively targeted without compromising systemic innate immune responses that are important for resistance to infection. This property could be exploited to mitigate injury‐ and disease‐associated inflammation in the brain without increasing susceptibility to systemic infection, an important complication in several neurological disorders.